2013
DOI: 10.1002/eji.201242563
|View full text |Cite
|
Sign up to set email alerts
|

Impact of preexisting memory to seasonal A/H1N1 influenza virus on the immune response following vaccination against avian A/H5N1 virus

Abstract: Cross-protection against divergent strains of influenza virus is an objective of various vaccination approaches. B cells cross-neutralizing several influenza A heterosubtypes have been isolated from cultured human memory B cells (MBCs) and plasmablasts early after influenza vaccination or infection.However, a systematic assessment of the frequency of MBCs and plasmablasts in the blood of healthy individuals is lacking. Here, we show that under resting conditions about 45% of human adults never vaccinated nor e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…1b). The moderate frequency of H5-specific memory B cells in subjects who were not exposed to H5N1 viruses or vaccines is likely a consequence of prior seasonal influenza vaccination and/or infection (18,19). Notably, at this time point there was no significant difference in the frequencies of H5-specific memory B cells between the H5N1 pLAIVprimed and unprimed or between the H5N1 pLAIV-primed and H7N3 pLAIV-primed subjects (P Ͼ 0.05, separate Mann-Whitney U tests) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1b). The moderate frequency of H5-specific memory B cells in subjects who were not exposed to H5N1 viruses or vaccines is likely a consequence of prior seasonal influenza vaccination and/or infection (18,19). Notably, at this time point there was no significant difference in the frequencies of H5-specific memory B cells between the H5N1 pLAIVprimed and unprimed or between the H5N1 pLAIV-primed and H7N3 pLAIV-primed subjects (P Ͼ 0.05, separate Mann-Whitney U tests) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Normally, the frequency of broadly neutralizing Abs that recognize highly conserved epitopes within the HA2 domain of the protein is very low and has been estimated to occur in only one in 100,000 HA-specific plasma cells (Corti et al, 2011). However, several studies have shown that these types of antibodies can be induced following heterologous primeboost vaccination and by using vaccine adjuvants that broaden heterosubtypic Ab responses (Buricchi et al, 2013; Chiu et al, 2013; Li et al, 2013). Thus, to enrich for cross-reactive Abs, mice were immunized with rHA isolated from 2 Group 1 HA viruses, VN1203 and CA07 virus, in the presence of the TLR4 adjuvant GLA-SE, which increases antibody repertoire diversity and enhances protection against heterosubtypic strains of H5N1 virus in mice and ferrets (Clegg et al, 2014; Clegg et al, 2012; Wiley et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…One can hypothesize that previous exposure to other subtypes may have offered protection against H5N1 [32].…”
Section: Discussionmentioning
confidence: 99%